2012
DOI: 10.1074/jbc.m112.361790
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Receptors Recognize the Mouse Genome through Binding Elements with Diverse Spacing and Topology

Abstract: Background: Retinoic acid receptors (RARs) heterodimerize with retinoid X receptors (RXRs) to regulate gene expression. Results: This heterodimer recognizes the genome via a large and diverse repertoire of direct and inverted repeat DNA elements. Conclusion:The observed diversity of binding elements changes the paradigm of how RAR-RXR recognizes the genome. Significance: Half-site spacing in the DNA binding element allosterically regulates RAR function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
163
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(172 citation statements)
references
References 44 publications
8
163
1
Order By: Relevance
“…S4). Underneath the apex of this peak, we discovered an inverted repeat consistent with IR0-type RAR elements (RAREs) (34,35). This IR0 element is highly conserved throughout eutherian mammals, including all four major superorders (Fig.…”
Section: Resultsmentioning
confidence: 85%
“…S4). Underneath the apex of this peak, we discovered an inverted repeat consistent with IR0-type RAR elements (RAREs) (34,35). This IR0 element is highly conserved throughout eutherian mammals, including all four major superorders (Fig.…”
Section: Resultsmentioning
confidence: 85%
“…As both receptors have essentially the same DNA recognition site (RGKTCA), a canonical retinoic acid response element (RARE) is usually two direct repeats of the recognition sequence, separated by a spacer region of variable length [68]. The use of chromatin immunoprecipitation (ChIP), however, with antibodies against RARs has demonstrated a much greater diversity of RAREs than previously appreciated, including direct repeats with no spacer [69]. There is also evidence that inverted repeats with no spacer can also the target for RARs [69].…”
Section: Interaction With Dnamentioning
confidence: 99%
“…The use of chromatin immunoprecipitation (ChIP), however, with antibodies against RARs has demonstrated a much greater diversity of RAREs than previously appreciated, including direct repeats with no spacer [69]. There is also evidence that inverted repeats with no spacer can also the target for RARs [69]. ChIP results also suggest that RA bound to receptors already on the promoter of target genes may not be representative of all of the potential targets.…”
Section: Interaction With Dnamentioning
confidence: 99%
See 1 more Smart Citation
“…RAREs are classically described as direct repeats of the hexameric motif (A/G) G(G/T) TCA separated by 1, 2, or 5 nucleotides (referred to as DR1, DR2, or DR5, respectively). [19][20][21] Recently, the recurrent motif (A/G) G(G/T) T(G/C) A, which differs from the classical consensus motif (A/G) G(G/T) TCA at position 5, with a G instead of a C, was reported from the alignment of several RAREs. 20) In a previous study, we also showed that RARα was involved in the induction of Tal2 in P19 cells after the addition of atRA and suspension culture for cell aggregation.…”
Section: Tal2mentioning
confidence: 99%